DXA-derived estimates of energy balance and its relationship with changes in body composition across a season in team sport athletes - Bartlett, J. D.; Hatfield, M.; Parker, B. B.; Roberts, L. A.; Minahan, C.; Morton, J. P.; Thornton, H. R. (European Journal of Sport Science, 2020)
This study examined the relationship between dual-energy x-ray absorptiometry (DXA)-derived estimates of energy balance (EB) and changes in body composition across various seasonal phases in team sport athletes. Forty-five Australian rules footballers underwent six DXA scans across a 12-month period (off-season [OS, Week 0-13], early [PS1, Week 13-22] and late pre-season [PS2, Week 22-31] and early [IS1, Week 3-42] and late in-season [IS2, Week 42-51]). EB (kcal·day-1) was estimated from changes in fat free soft tissue mass (FFSTM) and fat mass (FM) between scans according to a validated formula. An EB threshold of ± 123 kcal·day-1 for >60 days demonstrated a very likely (>95% probability) change in FFSTM (>1.0 kg) and FM (>0.7 kg). There were small to almost perfect relationships between EB and changes in FM (r = 0.97, 95% CI, 0.96-0.98), FFSTM (r = -0.41, -0.92 to -0.52) and body mass (r = 0.27, 0.14-0.40). EB was lowest during PS1 compared to all other phases (range, -265 to -142 kcal·day-1), with no other changes at any time. Increases in FFSTM were higher during OS compared to PS2 (1.6 ± 0.4 kg), and higher during PS1 compared to PS2, IS1, and IS2 (range, 1.6-2.1 kg). There were no changes during in-season (-0.1-0.05 kg). FM decreased only in PS1 compared to all other seasonal phases (-1.8 to -1.0 kg). Assessments of body composition can be used as a tool to estimate EB, which practically can be used to indicate athlete`s training and nutrition behaviours/practices.